Double Helical Rim Advancement Flaps With Scaphal Resection: Selected Cases Over 10 Years and Review of the Literature - TEZEL, ERDEM (SPRINGER, 2011)
Auricular surgery is a challenging subject in plastic surgery due to the complicated surface topography of the external ear. Although various techniques for ear reduction and helical rim reconstruction have been reported in the literature, an ideal method is yet to be defined. Double helical rim advancement flaps with scaphal resection presented in this report represent a practical technique for correcting macrotia and reconstructing helical rim defects. The amount of full-thickness resection at the helical rim is planned according to the desired reduction or extent of tumor. After helical excision, an incision that transects all the layers of the ear is carried out along the helical sulcus inferiorly and superiorly to yield two advancement flaps. Using scissors, a crescent from the scapha is excised through the full thickness of the ear. The flaps are approximated and sutured to the scapha by means of stitches that pass through skin and cartilage. The described technique has been performed successfully since 1998. It has been used for 12 cases of macrotia, 28 cases of tumor surgery, and 7 cases of ear reduction for asymmetric ears. No major complications have been encountered. Three cases are reported as examples of the procedure. Double helical rim advancement flaps with scaphal resection represent a versatile and safe technique that can be used for ear reduction, helical rim reconstruction, and correction for discrepancy in size of ears.
Keywords: Macrotia; Double helical rim advancement flaps; Ear reduction; Helical rim reconstruction; Ear reconstruction; EAR REDUCTION; MARGINAL DEFECTS; RECONSTRUCTION; OTOPLASTY; REPAIR